The presence of Pseudomonas aeruginosa in the dental unit waterline systems of teaching clinics - AS Al-Hiyasat (Journal compilation 2007 Blackwell Munksgaard, 2007)
The objective of this study was to evaluate the extent of Pseudomonas aeruginosa contamination of Dental Unit Water (DUW) at a Dental Teaching Center in Jordan.